The role of prefrontal cortex and serotonin in foraging decisions - Sarra, Dario (2022)
"Deciding whether to give up on a course of action or persist in the hope that our efforts will pay off is a crucial but hard problem to define and optimize. What information is best to take into account? What returns justify the costs? What are the costs and benefits of taking an alternative course of action? Considering all these questions simultaneously seems hard, yet, animals routinely solve this conundrum while foraging. Using behavioral, computational and neuronal activity manipulation techniques, in this thesis, we investigate how the brain solves this problem. Specifically, we aim to deepen our understanding of two aspects: how the agent represents the environment in order to extract information suitable to guide its foraging decisions, and how serotonin activity can bidirectionally modulate this decision process.(...)"